Experimental Study on Strengthening of RC Short Columns with BFRP Sheets - Krishna, Arathi; Mary Jacob, Milu; Saravana Raja Mohan, K (International Journal of Engineering and Technology, 2018)
Earlier the methods adopted for the repair and rehabilitation were the external bonding of the damaged component with steel fibers and steel jackets. But the major problem that caused due to this steel components is corrosion. Fiber Reinforced Polymer (FRP) composite materials used for strengthening of components in the form of confinement is of considerable importance in civil engineering. This paper presents the results of axially loaded RC short columns which are strengthened by providing confinement with new material BFRP. The primary objective of this work is to examine the load carrying capacity of concrete columns confined with basalt fiber reinforced polymer jacket (BFRP) which is considered as an abstruse material for strengthening. BFRP materials are non-corrosive, non-magnetic, and chemical resistant and they are progressively being used for repair, rehabilitation, and strengthening of structures that are not stable enough to carry loads. The parameters considered in the study are full and partial wrapping and the number of layers of confinement. The results obtained from the experimental studies and the analytical models precisely shows that the BFRP confinements will upgrade the compressive strength of columns under the given load condition.
Keywords: .